Evidence of neo-bureaucracy and institutional isomorphism in the implementation and functioning of the balanced scorecard: A case study - Isaias de Jesus Alvares Mendes Junior; Maria Do Céu Alves (Cogent Business & Management, 2023)
Recent years have seen constant pressure for more efficient management in the educational sector, and some studies have addressed the application of the Balanced Scorecard (BSC) in this sector. Analysis of this literature shows that theoretical developments in this research area are scarce, so this article aims to examine the presence of institutional isomorphism and neo-bureaucracy in the implementation and development of the BSC in a public educational institution in Brazil. It investigates how the presence of isomorphic pressure and neo-bureaucratic characteristics influence the implementation and development of the BSC in this sector. An interpretative approach was adopted to study this topic, resorting to a single case study. Data were gathered through semi-structured interviews and documentary analysis, and treated using qualitative analysis software, i.e., Nvivo, (QSR International, Version 10). The presence of neo-bureaucratic characteristics was found in the implementation and development of the BSC, with these characteristics contributing to the success of the tool in the teaching institution studied. We also found the presence of isomorphic pressure, in the decision to introduce the BSC, showing a clear presence of coercive isomorphism. However, as in any single case study, the results cannot be generalized.
Keywords: 650; balanced scorecard; education sector; institutional isomorphism; neo-bureaucracy; public sector